Cell Utilization Efficiency of Internet Protocol Traffic over Asynchronous Transfer Mode Networks - S., Janakiraman (1996)
In the near future, large computer networks will be connection oriented, with at least the data link connectivity being provided by the Asynchronous Transfer Mode. (ATM) networks. However, these networks may have to communicate with the existing network which predominantly use Internet Protocol (IP). Running Internet Protocol over Asynchronous Transfer Mode Network has been a contentious issue due to the inefficient segmentation of Internet Protocol packets into Asynchronous Transfer Mode (ATM) cells. In this thesis, the current protocols and standards pertaining to Internet Protocol over Asynchronous Transfer Mode are discussed and overheads involved in placing Internet Protocol packets into Asynchronous Transfer Mode cells, taking Logical Link Control/Sub Network Attachment Point Encapsulation into consideration, are analysed to find out the cell utilization of Asynchronous Transfer Mode cell in carrying the Internet Protocol packets. The Wide Area Network (WAN) oriented traffic for our analysis is collected from the Internet Traffic Archive. Analysis of the trace results show that the Asynchronous Transfer Mode cell utilisation is better in carrying the user information if the Internet Protocol packet are sizes larger. It is observed that ranges of Internet Protocol packets require similar number of Asynchronous Transfer Mode cells. At small values of Internet Protocol packets, the efficiency of Asynchronous Transfer Mode cell in carrying the user information is significantly low due to the Logical Link Control Encapsulation, padding and the trailer overheads. The Asynchronous Transfer Mode Cell utilization is better in Virtual Circuit (VC) based multiplexing, saving 8 bytes of encapsulation for each packet, thus improving the Asynchronous Transfer Mode (ATM) cell utilization marginally. It is seen that 80% of the Internet Protocol packet length varies from 54 to 200 bytes for which cell utilisation varies from 50%-to 82%. However, the average cell utilisation is 84% in the 20,000 packets observed since 20% of the Internet Protocol packet length is greater than 1000 bytes.